RELATIONSHIP OF QURAN AND THE SUNNAH: ANALYTICAL STUDY OF IBN AL-QAYYIM’S THOUGHTS - Dr. Hafiz Farhan Arshad; Dr. Muhammad Ihsan Ilahi; Dr. Sofia Mehboob; Dr. Muhammad Akram Virk; Dr. Waqas Ahmed; Ayesha Shabbir (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
Religion is a complete code of law and life. It has two basic sources and foundations: the Quran and the Hadith. The Prophet (peace and blessings of Allah be upon him) said: It is the clear fountain from which religious issues and the teachings of Islam are concluded. The Qur’an itself has stated this fact in several places.It is clear, therefore, that the only interpretation of the Quran would be reliable which would be transported by the Holy Prophet. If the Sunnah and Hadith were separated from Qura’an, then the Qur’an would not be able to be a complete code of Life. The Holy Qur’an is a book based on Allah’s principles and rules, and for the sake of explaining these principles, Allah has inspired His Prophet (peace and blessings of Allah be upon him). If Islam had only embraced the Qur’an, then it would not have been necessary for the revelation to be recited by The Holy Prophet. If Islam is based solely on Kitab ul Allah, then many rules cannot be practiced in religion. For example, the Qur’an has ordered the establishment of prayer but did not mention its times and procedures and all its problems. We have to refer to the Sunnah of Prophet SAW for the explanation and interpretation of this important pillar of Islam. Similarly, there is a case of zakat, which is commanded in the Book of Allah, but we are required of the Sunnah for all its rules and problems ۔For this reason, Qur’an has explained the principles of many aspects of Islam, but the interpretation does not exist in Kitab ul Allah. This is impossible without the correct interpretation of the Holy Prophet SAW. In the same way that the Qur’an is sent down by Allah Almighty, Hadith and Sunnah are the same. The Qur’an and the Sunnah have a great relationship, but they are inseparable. One is incomplete without the other.On this most important subject, the scholars of every period have written a lot in their own style. In this regard, Imam Ibn -Ul-Qayyim (may Allah have mercy on him) has recorded his opinion in this regard.The Sunnah cannot be separated from The Holy Qur’an in any case. The Sunnah is related Qur’an from these three types of Sunnah.